2017
DOI: 10.1080/15548627.2017.1345411
|View full text |Cite
|
Sign up to set email alerts
|

N-3 PUFAs induce inflammatory tolerance by formation of KEAP1-containing SQSTM1/p62-bodies and activation of NFE2L2

Abstract: Inflammation is crucial in the defense against infections but must be tightly controlled to limit detrimental hyperactivation. Our diet influences inflammatory processes and omega-3 polyunsaturated fatty acids (n-3 PUFAs) have known anti-inflammatory effects. The balance of pro- and anti-inflammatory processes is coordinated by macrophages and macroautophagy/autophagy has recently emerged as a cellular process that dampens inflammation. Here we report that the n-3 PUFA docosahexaenoic acid (DHA) transiently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 82 publications
1
35
0
Order By: Relevance
“…Autophagy has been shown to cause cell death along with apoptosis or ensure cell survival by inhibiting apoptosis [68]. Interestingly, it may even be a requirement for activating apoptosis in cells which are faced with stresses that can activate autophagy itself, such as oxidative stress or nutrient depravation [69,70]. Thus, although we observed activation of autophagy in the case of CDD as well as other plant organic fractions [52,53], it is not clear whether it was a requirement or a consequence of apoptotic cell death, manifesting as a cell survival response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy has been shown to cause cell death along with apoptosis or ensure cell survival by inhibiting apoptosis [68]. Interestingly, it may even be a requirement for activating apoptosis in cells which are faced with stresses that can activate autophagy itself, such as oxidative stress or nutrient depravation [69,70]. Thus, although we observed activation of autophagy in the case of CDD as well as other plant organic fractions [52,53], it is not clear whether it was a requirement or a consequence of apoptotic cell death, manifesting as a cell survival response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although we observed activation of autophagy in the case of CDD as well as other plant organic fractions [52,53], it is not clear whether it was a requirement or a consequence of apoptotic cell death, manifesting as a cell survival response. For example, it has been shown that oligomerization of SQATM1/p62 by oxidative stress is suggestive of induction of autophagy as a pro-survival mechanism rather than a cell death process [69,70]. Alternatively, it could also be an independent response to compounds in CDD or the other plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that the long chain n-3 PUFA, has antiangiogenic, anti-vasoproliferative, and neuroprotective actions on factors and processes implicated in the pathogenesis of degenerative/vascular retinal diseases of greatest public significance, including DR [ 18 ]. It has been demonstrated that diets with high levels of n-3 PUFA, have known anti-inflammatory properties [ 36 ] due to their ability to promote the gene expression of various inflammatory mediators via different intracellular signaling pathways [ 37 ] leading to the inhibition of the expressions of pro-inflammatory cytokines, leukocyte chemotaxis, and adhesion molecules. It is also known that they regulate the production of eicosanoids such as prostaglandins and leukotrienes and increase the synthesis of anti-inflammatory mediators such as resolvins, protectins, and maresins [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] Omega fatty acid has been suggested as an IOP reducing supplements [63][64][65] because of its anti-inflammatory effects. 66 Association of steroid derivative, estrogen with glaucoma has been previously explored with higher levels of estrogen in reduction in IOP and conferring a possible reduced risk of glaucoma. 67 The synthetic form of estrogen, estradiol, has been shown in a rat glaucoma model to inhibit optic nerve axonal degeneration by inducing a protein that is crucial in protecting RGC from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%